POLYMER PHYSICS AND COMPUTER MODELING OF POLYARYL ETHER (PAE)-BASED SUPERPLASTICIZERS - Mukhtarov, Nurdaulet (School of Engineering and Digital Sciences, 2023)
Superplasticizers play a significant role in concrete industry. They are the special type of chemical admixtures that reduce water-to-cement ratio, improve the workability of cement pastes, and have hydration retention capabilities. The novel type of superplasticizers, called polyaryl ether (PAE), is a special type of current state-of-the-art comb-like polycarboxylate ethers (PCEs). PAE is very similar to PCE, except for the backbone’s chemical nature. The aromacity of backbone increases the stiffness of backbone chain, which results in different adsorption behavior that might improve the particle dispersion of cement pastes and their rheology. Molecular Dynamics is a powerful tool that can be used to determine the structure and dynamics of various materials and processes on atomic scale, including the conformations of comb-shaped copolymer polyelectrolyte in free solution and adsorbed chain states. Unfortunately, the computational research of PAEs has not been extensive. In this work, the influence of backbone rigidity on conformational properties in free solution and adsorbed states of comb-like polyelectrolytes was studied by Coarse-Grained Molecular Dynamics simulations using the common structure of PCEs. Three comb configurations were constructed, each having different structural parameters n, N, and P. The simulations were performed in NVT ensemble with implicit solvent and explicit counterion methods. The results showed that radius of gyration of the comb in free solution gradually increases with the stiffness of the backbone and reaches a plateau at high rigidity. Moreover, the backbone flexibility affected the surface occupational area. The more rigid chains covered the more surface. The adsorption layer thickness was not affected by backbone flexibility when combs were fully adsorbed on the surface. These results coincided with polymer physics theories developed by Flatt et al., (2009) and Wang et al., (2018). Additionally, the grafting density affected the adsorption layer thickness. Comb configuration with lower N (higher grafting density) yielded smaller adsorption layer thickness, which could be due to stronger steric effect between adjacent sidechains. Observation of simulation snapshots revealed the influence of backbone charge density on the adsorption. Copolymers with lower charge density took longer time to adsorb on the surface due to weaker electrostatic interactions between backbone and surface.
Keywords: type of access: open access; superplasticizers; polyaryl ether (PAE); backbone stiffness; comb-like polymer; polymer physics; computer simulation; adsorption; conformation